EXPERIENCE WITH SPLENIC TRAUMA IN AYUB TEACHING HOSPITAL, ABBOTTABAD - Mufti, Tariq Saeed; Akbar, Ismail; Ahmed, Sajjad (Journal of Ayub Medical College Abbottabad, 2007)
Background: This study was carried out to estimate the prevalence, severity and mode of splenic trauma and management technique from amongst the abdominal trauma cases admitted in Ayub Teaching Hospital Methods: The study was carried out at Surgery units of Ayub Teaching Hospital, Abbottabad, the only referral hospital for major trauma cases, from July 2001 to Dec. 2002. One hundred consecutive abdominal trauma patients admitted to all surgical units which were followed up through complete documentation were included in the study. Their injuries were classified, treatment strategies outlined and complications were documented. Results: Out of the 100 patients presenting in emergency, 25% presented with blunt and 75% with penetrating trauma. 97 patients underwent laparotomy and 03 treated conservatively. Mean age was 27.26 (range 19-49) years. Out of these cases 19 patients had splenic injury, 6 (31.57%) with Type-I & II while 13 (68.42%) with Type-III & IV. 11(57.89%) of the splenic injuries were due to blunt abdominal trauma and 8 (42.10%) due to penetrating abdominal injuries. 14 (83.6%) of the patients with splenic injury underwent splenectomy and 5(26.3%) splenorrhaphy. Conclusion: The commonest cause of splenic injury was blunt abdominal trauma; Assessment of the severity of splenic injuries at the time of laparotomy resulted in splenic salvage procedures in some cases. Splenorraphy was associated with fewer complications. Keywords: Spleen; Trauma; Splenic Salvage